Even-skipped represses transcription by binding TATA binding protein and blocking the TFIID-TATA box interaction. - Li, C.; Manley, J.L. (Molecular and Cellular Biology, 1998)
The Drosophila homeodomain protein Even-skipped (Eve) is a transcriptional repressor, and previous studies have suggested that it functions by interfering with the basal transcription machinery. Here we describe experiments indicating that the mechanism of Eve repression involves a direct interaction with the TATA binding protein (TBP) that blocks binding of TBP-TFIID to the promoter. We first compared Eve activities in in vitro transcription systems reconstituted with either all the general transcription factors or only TBP, TFIIB, TFIIF30, and RNA polymerase II. In each case, equivalent and very efficient levels of repression were observed, indicating that no factors other than those in the minimal system are required for repression. We then show that Eve can function efficiently when its recognition sites are far from the promoter and that the same regions of Eve required for repression in vivo are necessary and sufficient for in vitro repression. This includes, in addition to an Ala-Pro-rich region, residues within the homeodomain. Using GAL4-Eve fusion proteins, we demonstrate that the homeodomain plays a role in repression in addition to DNA binding, which is to facilitate interaction with TBP. Single-round transcription experiments indicate that Eve must function prior to TBP binding to the promoter, suggesting a mechanism whereby Eve represses by competing with the TATA box for TBP binding. Consistent with this, excess TATA box-containing oligonucleotide is shown to specifically and efficiently disrupt the TBP-Eve interaction. Importantly, we show that Eve binds directly to TFIID and that this interaction can also be disrupted by the TATA oligonucleotide. We conclude that Eve represses transcription via a direct interaction with TBP that blocks TFIID binding to the promoter.